Planning method for joint operation of integrated energy storage system considering reliability - Xu, Yuanyuan (E3S web of conferences, 2023)
A joint operation planning method for integrated energy storage systems considering reliability is proposed. Firstly, the planning of the power exchange level of the energy storage system is achieved by calculating the optimal power exchange level of the supercapacitor, constructing a model for the optimal configuration of the two-layer energy storage, and using an algorithm for the solution of the model to optimise it. In the experiments, the joint operation planning performance of the proposed method is verified. The experimental results show that the model prediction accuracy is high when the proposed method is used for the joint planning of the integrated energy storage system, and has a more satisfactory joint operation planning performance.